Molecular Analysis Of Beta-Globin And Its Correlation With Serum Ferritin Levels In Beta-Thalassemia Patients In Punjab, Pakistan” (Journal of Pharmaceutical Negative Results, 2023)
Beta thalassemia is a major health concern in Pakistan due to inter-family marriages, lack of awareness, and high birth rates. Transfusion-dependent beta-thalassemia patients face severe iron overload which leads to multiple complications in their bodies. A total data of 96 transfusion-dependent patients with beta-thalassemia major were included in the study. Demographic data of patients were obtained by interviewing them. Statistical analysis showed that there is a statistically significant correlation between age and serum ferritin levels i.e. p = 0.006 and there is a statistically non-significant negative correlation between the frequency of blood transfusions and the levels of serum ferritin. Blood samples of beta thalassemia major patients were collected for DNA isolation and serum ferritin test. Primers were designed by using Primer3plus. PCR conditions were optimized to amplify the selected exonic regions. The secondary structures of proteins were obtained by using the sequence of samples by Psipred. trRosetta software was used to predict the 3D structure of the amplified gene and AutoDockvina predicted the interaction between the gene and ligands i.e. iron and oxygen. This interaction is carried out by molecular docking. Interaction between iron and HBB gene produce a binding affinity of -8.9 kcal/mol and the interaction between oxygen and HBB gene produced a binding affinity of -2.0 kcal/mol. These interactions showed that HBB is unable to bind with oxygen properly, which proves the deficiency of oxygen in beta-thalassemia patients despite multiple and consistent blood transfusions. This study is an attempt to understand the relationship between HBB gene, iron overload, and its clinical complications.